The relationship between thermal environments and clothing insulation for rural low-income residents in China in winter. (September 2019) - Zhao, Wei; Chow, David; Sharples, Steve
Abstract: China is developing rapidly, but there is an obvious imbalance in the development level between urban and rural areas. Differences in economics, living conditions and life style contribute to differences in indoor thermal environments, and may result in differences in the perceptions of thermal comfort between urban and rural areas. Clothing insulation as one of the most important parameters that affect thermal comfort is studied in this research. A field study is conducted in the rural areas of Lankao, China. A total of 384 valid samples were acquired. 54.97% researched houses suffered extreme cold indoor temperatures between 2°C and 6°C. Clothing insulation value of researched population is significantly larger than in other research. Clothing insulation value of female is significantly larger than that of male. It was also found that clothing insulation value correlates positively with age, that clo grow with the increase of age significantly. 7-days running mean outdoor temperature was selected from four temperature indices to predict clothing insulation value. Clo value is negatively correlated with 7-days RM outdoor temperature. But, the slope is quite small in such an extreme cold condition. A case study was conducted to estimate influence of adaptive clothing insulation on heating energy consumption (from Nov. to Mar.). Results show that 863 heating hours are reduced by using adaptive clothing insulation model. The total Heating Degree Hours (HDH) is reduced from 6445 to 1367 by 78.8% which means the same percentage of heating energy conservation. Besides, this case study also concluded that "adaptive clothing insulation model" has higher influence on heating energy consumption in transition season.